The Miracle from The Yard: Annona muricata as Cancer Chemo-Preventive and Co-Chemotherapy - Anwar Rovik; Riris Istighfari Jenie; Ratna Asmah Susidarti (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2025)
Cancer remains one of the biggest challenges to human health worldwide, with incidence and mortality rates continuing to rise. Popular cancer treatments to date include surgery, radiation-based therapy, chemotherapy, gene therapy, and hormone therapy. Chemotherapy is one of the primary treatment methods for cancer. However, it has unwanted side effects. It has prompted the search for new chemotherapeutic drugs with better efficacy, excellent selectivity, and fewer side effects. In recent years, there has been growing scientific interest in the potential of soursop leaf (Annona muricata) as an anticancer agent. This review paper discusses the phytochemical content of A. muricata and its potential as a co-chemotherapy against various types of cancer. Several bioactive compounds in soursop leaves have been reported, including annopentocin A, muricatetrocin A, annohexocin, isoannonacinone, annomuricin A, muricatin C, corossolin, and arianacin. Extracts from various parts of A. muricata have potential as co-chemotherapy in the treatment of breast cancer, colon cancer, prostate, lung, cervical, liver, and blood cancer. Studies concluded that A. muricata extracts have a good safety and tolerability profile. Its benefits as a co-chemotherapy agent will be even more significant when made into pharmaceutical dosage forms. A. muricata extracts or compounds packaged in pharmaceutical preparations are expected to improve patient's quality of life. However, more research is needed to determine the optimal dosage, route of administration, and potential side effects.